Back to the Basics: A COVID‐19 Surveillance Program Within a Local School District. (23rd February 2022) - Ganesh, Prakash R.; May, Ross; Dandurand, Mitch; Graham, Jeffrey; Rose, Johnie; Gullett, Heidi; Covell, Dave; Stange, Kurt C.
ABSTRACT: BACKGROUND: A school district in Northern Ohio implemented a COVID‐19 surveillance program from January 4 to May 21, 2021, as in‐person school and extracurricular activities resumed. METHODS: Among 560 staff members and >6300 students, random weekly testing was performed on 563 students and weekly for 204 students participating in extracurricular activities, and 553 staff. RESULTS: Cases of COVID‐19 were identified among 26 staff members and 23 students. Most of those infected were participating in extracurricular activities (14/23) and in the age range of 14‐18. Percent positivity was low (range 0.2‐2.4%) throughout the school surveillance program despite significant changes in positivity rate (2.8‐19.8%). CONCLUSION: This demonstrates that in a setting employing basic yet consistent mitigation strategies, there is low transmission among young children and adolescents as they return to in‐person classes and activities. Maintaining layered prevention strategies implemented and sustained with fidelity can substantially limit transmission within schools.